PENERAPAN MODEL PEMBELAJARAN BRAIN BASED LEARNING DENGAN TEKNIK PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VII.3 SMP NEGERI 5 PEKANBARU - Mulyani Tri Rahayu; Wan Syafi’i; Yustina Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to improve creative thinking skill of student class VII.3 SMP Negeri 5 Pekanbaru by implementation Brain Based Learning model with concept map technique. It had been done in SMP Negeri 5 Pekanbaru on January of April 2019. Parameters measure were student’s creative thinking skill. The type of research was classroom action research by implementation Brain Based Learning model with concept map technique. It had been done in two cylce with six of meeting’s and set done two basic competencies (KD) is KD. 3.10 and KD. 3.11. There wereplanning step, acting step, observation step and reflection step for each cycle. The research instrument used was a learning device that consist of a lesson plan, syllabus, assesment authentic sheet, observation sheet and creative thinking skill sheet. The collected data was analysed descriptively. The result of this research showed that student’achievement on first cycle was 84,28 with predicate C and increased on second cycle up to 90,05 with predicate B. Classical completeness percentage on both of cyclewas 100%. Student’s attitude on first cycle was 54,87 with predicate D and increased on second cycle up to 84,10 with predicate B. It can be conclude that Brain Based Learning model with concept map technique can improve student’achievement of student class VII.3 SMP Negeri 5 Pekanbaru.Key Words: Brain Based Learning, Student’s Achievement, Concept Map Technique